Implementasi Customer Relationship Management pada Platform Bisnis Wordpress - Prosarani, Ariadna (Ebiz Prima Nusa, 2022)
Along with the times in this era of globalization, business growth and development is getting faster. Lots of new companies are present around the community. In order to continue to survive in business competition, companies must quickly adapt to the current market conditions. Under these conditions, companies can not only rely on the products produced and offered to customers, but also have to build good relationships with all of their customers. Good relationships such as services and products that are in accordance with the needs and desires of consumers will give a feeling of satisfaction to customers. Customer satisfaction will have a positive impact on the company which in turn can maintain the sustainability of the company and increase profits. Current Customer Relationship Management (CRM) programs can be easily managed in businesses that use WordPress as a platform to help run the company. In WordPress, there are many tools (plugins) that can be used as a CRM system in an enterprise. A well-managed CRM will help companies create customer satisfaction. The CRM process is the process by which information about individual customers is turned into customer relationships. Companies with strong and good CRM will make customers more satisfied and loyal to the company. With CRM, companies will have clear information about who their customers are, what customers need, and what can increase customer satisfaction.